A study on the factors that influence customer awareness on canopy business : a case of nor canopy / Shahrul Syazwan Shahlan - Shahlan, Shahrul Syazwan (2017)
One of the most important parts in any business is the awareness of the firm by consumers. Awareness also is one of the most important elements in marketing. Therefore, factor that influences consumers' awareness on a canopy firm has attracted my attention and believes to be the most studied construct in marketing.